Synergistic Effect of Naringin and Glimepiride in Streptozotocin-induced Diabetic Rats - Rath, Deepankar; Kar, Biswakanth; Pattnaik, Gurudutta; Bhukta, Pallishree (Current Diabetes Reviews, 2024)
Objective: Evaluation of the synergistic effect of Naringin and Glimepiride in streptozotocin (STZ)-induced diabetic rats. Methods: Wistar rats were chosen and divided into five groups (n=6). STZ was used for the induction of diabetes. The combination of naringin and glimepiride was administered to diabetic rats. The changes in fasting blood sugar, body weight, Hb, HbA1c, and creatinine were evaluated, and urine was collected and the volume was observed. The lipid profiles like TC, HDL, LDL, and TG were measured. The biochemical parameters SGOT, SGPT, and ALP were analysed. Besides, endogenous antioxidant parameters like SOD, GSH, and catalase were also assessed. Lastly, the histopathological study of the beta cells in islets of the pancreas, glomerulus, and tubules of kidney and liver cells was conducted in all groups. Results: The result shows significant reduction (p<0.001) of blood sugar in the naringin and glimepiride-treated group when compared with the control group (diabetes). Additionally, the combination of Naringin (100 mg/kg) and Glimepiride (0.1 mg/kg) significantly restores the creatinine levels and urine volumes, SGOT, SGPT, and ALP when compared to a single dose of administration. Further, the abnormal lipid profile levels (TC, LDL, TG, and HDL), and endogenous antioxidant enzymes (SOD, GSH, catalase) in diabetic control rats were restored to normal levels in a significant manner. The histopathological result reveals significant alterations, including hypertrophy of islets and mild degeneration, renal necrosis, and inflammation of hepatocytes. Conclusion: A synergistic effect of Naringin and glimepiride was observed during the estimation of various biochemical parameters like body weight, fasting blood sugar, creatinine, urine level, TG, total cholesterol, SGOT, SGPT, ALP, Insulin, HbA1c, antioxidant parameters like SOD, GSH, and catalase in STZ-induced diabetic rats. Further, the combination of therapy improves the protective effect of the pancreas, kidney, and liver, suggesting a potential antidiabetic effect.
Keywords: synergistic effects